Elementary Korean - King, Ross, 1961- (Tuttle language library., 2009)
This is a comprehensive and detailed introductory Korean textbook and language learning package. Korean is now the 15th most popular language taught at American universities. This new edition of Elementary Korean, the most comprehensive and detailed introductory Korean textbook available, offers beginning learners of Korean everything they need to learn the language effectively. Perfect for a first-year university-level course use or for the independent language learner. No prior knowledge of the language is necessary. The new format, now with dozens of illustrations, presents Korean vocabular.